Critical Thinking Pada Peserta Didik: Refleksi Surah Al-An’am Ayat 74-79 Dalam Konteks Abad 21 - Muflihah; Ilma Rasyida, Nadya; Azizah, Nurul; Karman (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2023)
This research aims to examine the aspect of critical thinking among learners from the perspective of the Qur'an, specifically in Surah al-An'am verses 74-79, and its reflection in facing the challenges of the 21st century. This study is a literature review, utilizing a qualitative approach. The analysis was conducted using data from relevant sources related to the issues discussed, such as the Qur'an, books, articles, and research findings. The results of this research indicate that the aspect of critical thinking in Surah al-An'am verses 74-76 can be identified based on six core critical thinking skills, namely interpretation, analysis, evaluation, inference, explanation, and self-regulation. The reflection from Surah al-An'am verses 74-79 reveals that the critical thinking abilities expressed in these verses can provide solutions to the challenges arising in the 21st century, especially in the field of education. These competencies can assist in the development of learners' character and ethics, sharpen learners' thinking and analytical skills, enhance problem-solving abilities, and shape analytical skills in line with the demands of the 21st-century workforce